PERAN MASYARAKAT DALAM MENUNJANG KEBERLANJUTAN DESTINASI WISATA BELANJA KOTA BONTANG KALIMANTAN TIMUR - Lapotulo , Nensi; Gunawan , Agung Arif; Simatupang , Devid Trinaldo; Kurnia , Okki; Gobalan, Simran; Afriani, Miratia (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to analyse the role of the community in supporting the sustainability of shopping tourism destinations in Bontang City, East Kalimantan. A qualitative approach was employed, utilising a content analysis method, on 30 online documents comprising news articles, government reports, scientific journals, and digital content from 2018 to 2025. The results reveal three primary themes: the pandemic's impact on the economy, government policies, and community social support. The findings show that the social, cultural, and economic strengths of local communities are the foundation for the sustainability of shopping tourism. This study emphasises the importance of collaboration between the community, government, and business actors in building community-based tourism destinations.